Evolving Roles of Notch Signaling in Cortical Development - Nian, Fang-Shin; Hou, Pei-Shan (Frontiers in Neuroscience, 2022)
Expansion of the neocortex is thought to pave the way towards acquisition of higher cognitive functions in mammals. The highly conserved Notch signaling pathway plays a crucial role in this process by regulating the size of the cortical progenitor pool, in part by controlling the balance between self-renewal and differentiation. In this review, we introduce the components of Notch signaling pathway as well as the different mode of molecular mechanisms, including trans- and cis-regulatory processes. We focused on the recent findings with regard to the expression pattern and levels in regulating neocortical formation in mammals and its interactions with other known signaling pathways, including Slit-Robo signaling and Shh signaling. Finally, we review the functions of Notch signaling pathway in different species as well as other developmental process, mainly somitogenesis, to discuss how modifications to the Notch signaling pathway can drive the evolution of the neocortex.